2006
DOI: 10.1002/pssc.200562741
|View full text |Cite
|
Sign up to set email alerts
|

Magnetoresistance and Hall effect of a 2DEG in GaAs/AlGaAs: electron interaction and ‘memory’ effects in the presence of a mixed disorder

Abstract: We have studied the corrections to the Drude conductivity and Hall constant of a high-mobility twodimensional electron gas in a GaAs/AlGaAs heterostructure due to the electron-electron interaction in the presence of a mixed disorder. A parabolic, negative, temperature-dependent magnetoresistance (MR) and temperature-dependent Hall constant are observed. We show that these effects can be explained in terms of the electron interaction theory and obtain the values of the Fermi-liquid interaction parameter F σ o .… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
(15 reference statements)
1
3
1
Order By: Relevance
“…The suppression of the MR as T increases, observed by Galaktionov et al (2006) in samples similar to those in (Li et al, 2003) in a wider range of T τ 1, agrees favorably with the T −1/2 scaling characteristic of the ballistic regime. The enhancement of the MR compared to Eq.…”
Section: Quantum Magnetoresistancesupporting
confidence: 75%
See 2 more Smart Citations
“…The suppression of the MR as T increases, observed by Galaktionov et al (2006) in samples similar to those in (Li et al, 2003) in a wider range of T τ 1, agrees favorably with the T −1/2 scaling characteristic of the ballistic regime. The enhancement of the MR compared to Eq.…”
Section: Quantum Magnetoresistancesupporting
confidence: 75%
“…II.C). A growth of ρ xx with increasing B in the experiments by Dai et al (2010) and Hatke et al (2011b) was observed in a range of B well before the onset of oscillations [see also the earlier results (e.g., Galaktionov et al, 2006) on a positive MR observed at sufficiently high T in moderate-mobility structures]. The huge negative MR observed by Dai et al (2010) and Hatke et al (2011bHatke et al ( , 2012c, as well as the growth of ρ xx at higher B, warrants further study.…”
Section: Classical Magnetoresistancementioning
confidence: 51%
See 1 more Smart Citation
“…The narrow peak is quite robust with respect to thermal activation and additional in-plane magnetic fields. This phenomenology is different than that one of similarly textured peaks observed in samples of lower mobilities and larger interaction parameters [10,11], where the narrow peak is strongly temperature dependent and can be explained by weak localization.…”
Section: Introductioncontrasting
confidence: 79%
“…The result is plotted in Fig. 2b for sample D4, showing a Drude-like response with very little dependence on B except near B = 0 T where quantum phase coherent effects such as weak localization [21][22][23] and memory effects [24][25][26][27] as well as electron-electron interactions [28,29] may play a role. We will there -FIG.…”
mentioning
confidence: 99%